2007
DOI: 10.1016/j.nlm.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The genetic versus pharmacological invalidation of the cannabinoid CB1 receptor results in differential effects on ‘non-associative’ memory and forebrain monoamine concentrations in mice

Abstract: The endocannabinoid CB1 receptor has been implicated in the inhibitory control of learning and memory. In the present experiment, we compared the behavioral response of CB1 receptor knockout mice (CB1R-/-) with animals administered CB1 receptor antagonist/inverse agonist SR141716A (rimonabant; 3 mg/kg IP, 30 min pre-trial) in terms of acquisition and retention of a habituation task and changes in cerebral monoamines. The results can be summarized as follows: (i.) The acute and chronic invalidation of the CB1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Several studies reported increased anxiety-related behaviors after impaired CB1R signaling only when aversive stimulus cannot be avoided (Haller et al, 2004, 2009; Thiemann et al, 2007; Kamprath et al, 2009). However, little is known about how ECS modulation of the DAergic system could be involved in this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported increased anxiety-related behaviors after impaired CB1R signaling only when aversive stimulus cannot be avoided (Haller et al, 2004, 2009; Thiemann et al, 2007; Kamprath et al, 2009). However, little is known about how ECS modulation of the DAergic system could be involved in this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is the option that endocannabinoids modulate one-trial sensitization via their influence on memory processes (Riedel & Davies 2005). Attenuated CB1 signalling seems to coincide, among others, with increased short-term (Degroot et al 2005) and long-term habituation (Thiemann et al 2007) to an open field. Our data partially support these observations: Total-CB1-KO showed pronounced within-exposure habituation in the open field under bright light, but no differences to wild-type controls Genes, Brain and Behavior (2009) 8: 685-698 in between-exposure habituation.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed with mice lacking CB1 expression in the entire body (Total‐CB1‐KO; Marsicano et al 2002) or specifically in glutamatergic cortical neurons (CB 1 f/f;Nex−Cre = Glu‐CB1‐KO; Monory et al 2006). Because the endocannabinoid system was shown to mediate habituation to homotypic stressors (Patel et al 2005; Patel & Hillard 2008), including adaptation to aversive tones (Kamprath et al 2006), and to play a particular role during re‐exposure to exploration‐based anxiety tests, such as the elevated plus‐maze test (Rodgers et al 2005) and the open field test (Thiemann et al 2007), we additionally studied the consequences of repeated testing (i.e. familiarity) for test situations with avoidable (elevated plus‐maze) or unavoidable (open field) light exposure.…”
mentioning
confidence: 99%
“…The fact that these effects were blocked by the administration of CB 1 r-antagonist, SR141716A, supports CB 1 r as being the target involved in the acute effects of cannabinoids on memory impairments (Da and Takahashi, 2002;Pamplona and Takahashi, 2006). Interestingly, pharmacological or genetic disruption of CB 1 r signaling enhances learning and memory in a variety of spatial and operant paradigms (Thiemann et al, 2007). Further studies revealed the modulation of GABA neurotransmission through the activation of CB 1 r located on GABA interneurons, the indirect activation of the mammalian target of rapamycin (mTOR)/70-kDa ribosomal protein S6 kinase (p70S6K) signaling cascade and NMDA receptors as the main mechanisms underlying the cognitive impairments produced by cannabinoids (Puighermanal et al, 2009).…”
Section: Introductionmentioning
confidence: 93%